A study on the evidence-based healthcare practice in selected hospital libraries in Metro Manila and the perceived professional competence of hospital medical librarians towards the evolving role of medical librarianship - Roque, Maria Criselda C.; Encanto, Joenabie A. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2003)
During the recent years, the rise of the evidence-based practice appears to fit well for medical librarians. The emergence of Evidence-based medicine (EBM) and Evidence-based healthcare (EBHC) practice in the medical profession has brought to the fore the role of medical librarians in its practice, and has called for a stronger integration of the librarian in the healthcare process. With changes brought about by advancements in technology and proliferation of information in the field of healthcare, a need is created for redefining medical librarianship towards an increasing emphasis in the professional role on issues such as information literacy and other pedagogical aspects related to searching information to assist medical practitioners.
This study made use of the descriptive-qualitative method of research. Through a structured survey questionnaire consisting of seven (7) parts with close and open-ended questions, the study explored the level of practice and perceived professional competence of hospital medical librarians towards performing roles related to EBHC practice, and also their awareness and practical knowledge of the field. The respondents are library personnel working at government and private hospitals in Metro Manila, including licensed, unlicensed, and graduate students of Library and Information Science (LIS) and other similar or equivalent courses. Quantitative research techniques were employed particularly the Likert's Scale. The mean point value, frequencies and percentage distribution were used to analyze the data gathered.
Based on this study, the following main results were found: (1) Majority of the respondents are familiar with EBHC (10 or 62.5%) as a concept, while most of them are aware of their role in supporting EBHC practice in their workplace. (2) Majority of the respondents (11 or 68.75%) have a positive perception towards EBHC practice as a concept and to its application related to medical librarianship. (3) Majority of the respondents (13 or 81.25%) are confident and eager to engage in the emerging roles of librarians in supporting EBHC practice. (4) Overall, the respondents have novice proficiency level in performing roles related to EBHC practice (average mean point value of 3.13). Based on the proficiency scale used, this means that they understand and can discuss terminology, concepts, principles, and issues related to this competency, but still have limited experience. (5) Hospital medical librarians identified lack of institutional support for the EBHC program as the most significant barrier to hospital medical librarians' engagement with EBHC practice, and also to the potential future widespread implementation of librarians' roles related to it.
When it comes to work output, it can be inferred that medical librarians currently allot more time in doing traditional library roles compared to performing roles related to EBHC practice. Bulk of the traditional services that hospital medical librarians perform includes reference service, circulation service and literature alerting services. It is notable, however, that the medical librarians also reported that they perform tasks related to EBHC practice. The most frequently performed tasks include helping physicians and other health professionals by providing EBM literature, providing end-user searching training, and assisting in research projects related to EBHC.
On the basis of findings and conclusions taken from the study, the following recommendations were given by the researcher for consideration: (1) Improve initial campaigns that are geared towards increasing awareness among the librarians about the developments in their profession, particularly in evidence-based healthcare (EBHC) practice through more seminars, workshops and talks conducted regularly by LIS organizations or individual libraries, and encouraging the participation of medical librarians; (2) Creating credentialing programs could be developed so as to give formal recognition of medical librarians' specialty; (3) Reassess the content of Library and Information Science (LIS) education curricula both in the undergraduate and postgraduate study (masters level) to allow changes that could meet the professional needs and skills required for those who would like to pursue medical librarianship.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Medical librarians -- Philippines -- Manila Metropolitan Area; Hospital libraries -- Philippines -- Manila Metropolitan Area -- Use studies